AB1427-HPR "it gets me down every single day": are men with RA getting the support they need?. (23rd January 2014) - Flurey, C.A.; Morris, M.; Pollock, J.; Hughes, R.; Richards, P.; Hewlett, S.
Abstract : Background: Daily life with RA has been explained as unpredictable and full of uncertainty. However, most research about daily life with RA was conducted before current more aggressive medications, and in women. Objectives: To explore daily life on modern therapies. Methods: Q-Methodology: 30 RA patients sorted 39 statements (generated from previous qualitative interviews) about daily life with RA across a forced distribution, in ranked order of agreement. Data were analysed using centroid factor analysis with varimax rotation (i.e. the participants and not the items are the variables). Demographic and clinical data were collected and patients completed comments booklets about their rationale for sorting the statements. Results: Three factors were generated, which explained 33% of the study variance and accounted for 23 of the 30 participants. None of the Q-sorts were confounded (loading on more than one factor). A participant loading of 0.41 reached significance at p<.01. Factor A (Taking Control: "Just a fact of life") and Factor B (Keeping RA in its place: "It's a very small part of you") were predominately female participants (86%, 100%) and have been reported previously. Factor C: Struggling Through: "It gets me down every single day" comprised 8 participants, 63% male: mean disease duration 15.3yrs (SD 14.3), age 55.5yrs (SD 7.1), HAQ score 1.3 (SD 0.9), patient global 4.8 (SD 2.5), 50% on biologic therapies. These predominantly male patients are never symptom free, experiencing pain and fatigue daily: "It's like feeling ill all the time", they describe fatigue as "the worst symptom". They worry and get angry and frustrated about their RA: "I get very frustrated with it, the problem is then I get irritated and take it out on the wife" . This group report being unable to effectively manage their symptoms, some "don't know what to avoid", whilst others use unadvisable methods: "I find cocaine numbs the pain" . They report being unable to be spontaneous or to exercise and they struggle to explain their experience to their family. These patients feel their body has let them down, life is unfair: "Why me? Why now?" and the idea that they are lucky in comparison to others is "ridiculous" . We re-examined the preceding qualitative interviews that generated these Q-statements, and this clarified these men's views further. Having RA means men's traditional masculine coping strategies have to be adapted: "you can't go and thump a wall because you end up with a flare and you can't go and kick a football around or anything like that, so you need to find an outlet and talking is the outlet I suppose" . At the same time, they reject those traditional, more female-gendered RA support mechanisms: "The self help groups don't confront it enough, it might be all lovey dovey [sweet and gentle] but sometimes you have got to be quite hard about it". Conclusions: Whilst some patients cope well with their RA, others struggle to accept and adapt to their condition; the majority of these being male. These findings indicate a need to address the unique support needs of men with RA and to consider providing support that is acceptable to their masculine identities. Disclosure of Interest: None Declared